Enzyme-linked immunosorbent assay (ELISA) for the anthropogenic marker isolithocholic acid in water. (1st November 2016) - Baldofski, Stefanie; Hoffmann, Holger; Lehmann, Andreas; Breitfeld, Stefan; Garbe, Leif-Alexander; Schneider, Rudolf J.
Abstract: Bile acids are promising chemical markers to assess the pollution of water samples with fecal material. This study describes the optimization and validation of a direct competitive enzyme-linked immunosorbent assay for the bile acid isolithocholic acid (ILA). The quantification range of the optimized assay was between 0.09 and 15 μg/L. The assay was applied to environmental water samples. Most studies until now were focused on bile acid fractions in the particulate phase of water samples. In order to avoid tedious sample preparation, we undertook to evaluate the dynamics and significance of ILA levels in the aqueous phase. Very low concentrations in tap and surface water samples made a pre-concentration step necessary for this matrix as well as for wastewater treatment plant (WWTP) effluent. Mean recoveries for spiked water samples were between 97% and 109% for tap water and WWTP influent samples and between 102% and 136% for WWTP effluent samples. 90th percentiles of intra-plate and inter-plate coefficients of variation were below 10% for influents and below 20% for effluents and surface water. ILA concentrations were quantified in the range of 33–72 μg/L in influent, 21–49 ng/L in effluent and 18–48 ng/L in surface water samples. During wastewater treatment the ILA levels were reduced by more than 99%. ILA concentrations of influents determined by ELISA and LC-MS/MS were in good agreement. However, findings in LC-ELISA experiments suggest that the true ILA levels in concentrated samples are lower due to interfering effects of matrix compounds and/or cross-reactants. Yet, the ELISA will be a valuable tool for the performance check and comparison of WWTPs and the localization of fecal matter input into surface waters. Highlights: Isolithocholic acid (ILA), a bile acid, is a promising fecal marker. ILA levels were reduced by more than 99% in wastewater treatment plants (WWTPs). ILA concentrations of 33–72 μg/L in WWTP influents were determined. ILA concentrations of 21–49 ng/L in WWTP effluent and surface waters were determined. The performance of wastewater treatment plants can be monitored with the ILA ELISA.